Which cognitive and perceptual skills best discriminate elite female handball players - Biscaia, Paula (Array, 2021)
The purpose of this study was to identify which cognitive and perceptual skills best discriminate elite female handball players according to the age group to which they belong to. The sample consisted of 73 Portuguese national teams" female handball players, aged between 11 and 29 years, with an average of 7.5 (± 3.7) years of practice. The following tests were applied: Thurstone Identical Figures Test, Toulouse-Piéron Concentrated Attention Test, and the Nideffer Attentional and Interpersonal Style Inventory to evaluate perceptual skills, the polyreactiometer for Windows – PRWin to evaluate information processing, and an evaluation protocol for precision in anticipation using the temporal occlusion paradigm. The interpretation of the obtained discriminant function was based on the structure of the coefficients greater than |0.30|. The Seniors" age group is discriminated from that of Talents by their better reaction, perception, and attention times, namely, by the ability to integrate several stimuli simultaneously and by a better capacity to anticipate future events more accurately. This discriminating model can help coaches recruit players as well as improve psychological training programmes.